A systemic analysis of patients undergoing open ventral hernia repair (2011-2017) - Choudhry, Esha A.; Sheth, Jenish Y.; Darshan, Jitendra R. (International Surgery Journal, 2018)
Background: The use of prosthetic mesh for reinforcing a hernia repair is considered most valid. Controversy exists regarding the use of the type of meshplasty. An insufficient evidence exists as to which type of mesh and mesh position (onlay, inlay, sublay (retrorectus) or preperitoneal) should be used. The effectiveness these methods have been systematically analysed in order to accelerate functional recovery and shorten hospitalization in patients undergoing open ventral hernia repair (VHR). Methods: This was a Prospective randomized single blinded comparative study conducted in the Department of Surgery at SMIMER hospital, Surat for patients presenting with the complaint of anterior abdominal wall hernia over a duration of 6 years (September 2011 - September 2017) with an average follow up period of 12 months, including 318 adult patients. All patients were preoperatively assessed clinically and by ultrasonography to confirm the diagnosis and randomized for open VHR after obtaining a well-informed written consent and satisfying the inclusion and exclusion criteria. 67% Patients (213/318) underwent retrorectus Meshplasty and were categorized into group A. The rest underwent Onlay (16.3% - 52/318)/Inlay (4.7% - 15/318)/Preperitoneal Meshplasty (11.9%-38/318) and were collectively (33% (105/318)) categorized into group B. Both Groups were Compared in terms differences in intra operative timing, intra operative complications, immediate post-operative outcome, early and delayed post- operative complications including readmission and recurrence rates. Results: Authors observed significantly lesser post-operative pain, higher well being, reduced wound complications and recurrence rate in group A. Mean duration of surgery was insignificantly higher for retrorectus meshplasty. Conclusions: Despite each method having its own advantages and disadvantages, retrorectus mesh repair was found superior because the mesh is placed with significant overlap under the muscular abdominal wall.